Autonomous bus in 3D simulation environments - Xiang, Zhou (2018)
With the rapid development of Artificial Intelligence, the Autonomous Vehicle Technology has gained a huge amount of attention. However. it is extremely time-consuming and of high-cost to design, develop, manufacture and test the actual autonomous vehicle in real world. A proper simulation for autonomous vehicle based on physical simulation engine, such as gazebo, which allows match the actual situation and checking of performance before the actual production and manufacturing of the real autonomous vehicle. In this dissertation, the main target was to build a 3D model in a virtual environment based on Gazebo for the target autonomous bus, where several simulated sensors such as Lidar, sonar, camera, Global Position System and Inertial Measurement Unit for sensing object's acceleration velocity will be added to the intended 3D bus model to capture real-time that are generated by simulated sensors. Meanwhile, the Robot Operating System (ROS) will be applied to add the ROS nodes to the 3D bus model for the further data visualization based on 3D visualizer, such as Rviz, and communication between these corresponding nodes of sensors. Lastly. Based on the existing drawbacks of communication mechanism in ROS, a corresponding method has been proposed to improve this defect. Besides, the general simulation performance for this 3D autonomous bus model based on Gazebo and ROS will be analyzed.